ECOTOURISM AND SUSTAINABLE DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Most governments, local organizations, tourism agents, and scholars have extensively promoted ecotourism in recent years. However, government policies have been ignored, public opinion has not been updated, the local tourism infrastructure is incomplete, and operational practices have been poor for a long time. This is because ecotourism has not made any empirical profits, and additionally, it has even incurred more practical costs, which have encouraged few tourism agents to execute and operate ecotourism correctly. The contributive findings of this study are the following: (1) Beyond the evaluated measurements of quantitative and qualitative analyses, the sustainable development of ecotourism essentially creates benefits for the local industry and the environment, and actively assists the industry in improving the business environment, in enhancing service quality, and in creating ecotourism benefits. (2) It is very apparent that the tourism offices of central and local governments, as well as related travel agents and local organizations, have to be trained with regard to the appropriate consumption of sightseeing products, with a consideration of productive yield and a critical focus on quality instead of quantity.